Tidal signatures in sand prone, tectonically generated Jurassic straits, Scotland ... - Blackwood, Stuart, 1972- (The University of Texas at Austin, 2006)
The Mid-Jurassic Bearreraig Formation is superbly well exposed on the Isles of Skye and Raasay in NW Scotland. In southern Skye the Bearreraig displays a spectacular, cyclical hierarchy of sand rich, tide-generated bedforms: 1. Upward thickening to thinning compound and compound-compound trough cross-sets (3D dunes) up to 2.5m thick 2. Compound trough cross-sets (3D dunes) up to 10m thick 3. Upward thinning, simple and compound planer cross-sets (2D dunes) up to 50cm thick Tectonically-generated sequences (up to 140m thick) consisting of these three dune types can be recognized within the formation. Sedimentation occurred in NNE-SSW-aligned, North Skye/Raasay and South Skye half-grabens, defined by Aalenian-Bajocian faulting associated with the initial opening of the North Atlantic. SSW oriented (S. Skye) and NNE oriented (N. Skye/Raasay) fault-parallel paleocurrent directions (indicative of basin separation) suggest that the faults were active and had enough topographic expression to enhance the tidal ...